Identification of sucrose synthase from Micractinium conductrix to favor biocatalytic glycosylation - Chen, Kai; Lin, Lei; Ma, Ruiqi; Ding, Jiajie; Pan, Huayi; Tao, Yehui; Li, Yan; Jia, Honghua (Frontiers in Microbiology, 2023)
Sucrose synthase (SuSy, EC 2.4.1.13) is a unique glycosyltransferase (GT) for developing cost-effective glycosylation processes. Up to now, some SuSys derived from plants and bacteria have been used to recycle uridine 5’-diphosphate glucose in the reactions catalyzed by Leloir GTs. In this study, after sequence mining and experimental verification, a SuSy from Micractinium conductrix (McSuSy), a single-cell green alga, was overexpressed in Escherichia coli, and its enzymatic properties were characterized. In the direction of sucrose cleavage, the specific activity of the recombinant McSuSy is 9.39 U/mg at 37 °C and pH 7.0, and the optimum temperature and pH were 60 °C and pH 7.0, respectively. Its nucleotide preference for uridine 5'-diphosphate (UDP) was similar to plant SuSys, and the enzyme activity remained relatively high when the DMSO concentration below 25%. The mutation of the predicted N-terminal phosphorylation site (S31D) significantly stimulated the activity of McSuSy. When the mutant S31D of McSuSy was applied by coupling the engineered Stevia glycosyltransferase UGT76G1 in a one-pot two-enzyme reaction at 10% DMSO, 50 g/L rebaudioside E was transformed into 51.06 g/L rebaudioside M in 57 h by means of batch feeding, with a yield of 76.48%. This work may reveal the lower eukaryotes as a promising resource for SuSys of industrial interest.